2017
DOI: 10.1016/j.jpurol.2016.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after pediatric open, laparoscopic, and robotic pyeloplasty at academic institutions

Abstract: Summary Introduction Patient age and hospital volume have been shown to affect perioperative outcomes after pediatric pyeloplasty. However, to date, there are few multicenter studies that focus on outcomes at teaching hospitals, where many of the operations are performed. Objective The goal was to determine if surgical approach, age, case volume, or other factors influence perioperative outcomes in a large contemporary cohort. Study design Using the clinical database/resource manager (CDB/RM) of the Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 27 publications
(36 reference statements)
0
23
0
4
Order By: Relevance
“…30 We found an overall complication rate of 15% within the initial hospital stay, which was higher than rates of others reporting on 2.1 to 5% in open and 2.2 to 2.5% in laparoscopic pyeloplasty. 12,27 The higher percentage in our study population might be explained by a more inclusive definition of complications (including minor complications, such as wound infection) based on ICD10 codes. Logistic regression analysis however revealed that the risk for complications was independent from the surgical technique applied and the age of the patients at surgery, which is in line with other reports.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…30 We found an overall complication rate of 15% within the initial hospital stay, which was higher than rates of others reporting on 2.1 to 5% in open and 2.2 to 2.5% in laparoscopic pyeloplasty. 12,27 The higher percentage in our study population might be explained by a more inclusive definition of complications (including minor complications, such as wound infection) based on ICD10 codes. Logistic regression analysis however revealed that the risk for complications was independent from the surgical technique applied and the age of the patients at surgery, which is in line with other reports.…”
Section: Discussionmentioning
confidence: 94%
“…24 In line with our findings, Chan et al reported a 14% shorter LOS in children up to 5 years of age undergoing robotic laparoscopic pyeloplasty. 27 Taking LOS as an indicator for well-being, one may speculate that LP is superior compared with an open approach especially in infants up to 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DOI:10.21886/2306DOI:10.21886/ -6424-2017 Введение В детской хирургии основным направле-нием является поиск и внедрение ма-лоинвазивных методов лечения. При врожденных пороках развития органов моче-выделительного тракта, в первую очередь, об-струкции лоханочно-мочеточникового сегмента (ЛМС), лапароскопические и ретроперитоне-оскопические методы стали занимать главен-ствующую позицию [1,2]. И сегодня эти виды эндовидеохирургического лечения можно уже считать «золотым стандартом» при лечении данной проблемы.…”
Section: Endoscopic High Pressure Balloon Dilitation As a Methods Ofunclassified
“…The main difference between the two approaches was operative time and cost, with robotic significantly slower and more expensive. Other multi-centre studies since then have shown some reduction in hospital stay [8,9] but a multi-centre prospective RCT trial would be needed to accurately compare the laparoscopic and the robotic approach.…”
Section: Pyeloplastymentioning
confidence: 99%